Analisis Pengaruh BI Rate, Inflasi, dan Indeks Harga Konsumen terhadap Indeks Harga Saham Komposit di Indonesia Periode 2019-2024 - Edgina Aurellia Prasetyo; Amandamayakosa Kartawijaya; Ajeng Faiza Nijma Ilma; Dijan Rahajuni (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of the BI Rate, inflation, and Consumer Price Index (CPI) on the Composite Stock Price Index (IHSG) in Indonesia during the 2019–2024 period, within the context of financial system stability and development economics. The background of this study is rooted in the critical role of monetary policy and price dynamics in maintaining capital market stability, particularly following global economic pressures and the COVID-19 pandemic that disrupted the national financial sector. The methodology employed is quantitative analysis using multiple linear regression with secondary data sourced from Bank Indonesia, Statistics Indonesia (BPS), and the Indonesia Stock Exchange (IDX). The findings reveal that the BI Rate has a significant effect on the IHSG, inflation exhibits a negative or unstable influence on IHSG movements, while the CPI serves as a price pressure indicator that also impacts stock index dynamics. These results support the Monetary Policy Transmission Mechanism theory through the asset price channel, wherein the BI Rate influences the IHSG via changes in investor expectations and asset valuation, with inflation and CPI acting as intermediate targets that moderate these dynamics. This study provides insights for strengthening monetary policy and formulating sustainable economic development strategies in Indonesia